Chemical Composition of Nigella sativa L. Seeds Used as a Medical Aromatic Plant from East Anatolia Region, Turkey - Vatansev, Husamettin; Ciftci, Harun; Ozkaya, Ahmet; Ozturk, Bahadir; Evliyaoglu, Nurcan; Kiyici, Aysel (Asian Journal of Chemistry, 2013)
In this study, chemical composition such as vitamins, fatty acids and trace elements of Nigella sativa L. seeds collected from East Anatolia Region of Turkey were investigated. Fatty acids in the lipid extracts were converted into methyl esters. The methyl esters were extracted with n-hexane, they were separated and quantified by gas chromatography. Fat soluble vitamins were determined by HPLC and the mixture of acetonitrile/methanol (3/1, v/v) was used as the mobile phase. For determination of trace elements levels, solutions from microwave digestion of a certain amount of seeds were analyzed with inductively coupled plasma optical emission spectrometry. Main fatty acids of Nigella sativa L. seeds were found as 66.5 and 23.5 (as relative % peak area) for linoleic acid (18:2) and oleic acid (18:1), respectively. The contents of Co, Ni, Fe, Zn, Cu, Mn and Cr were determined as 0.12, 1.48, 117.32, 41.42, 30.26, 28.56 and 2.55 μg/g (dry matter) respectively. The levels of vitamins were found as 10.19 μg/g for a-tocopherol, 2.28 μg/g for d-tocopherol, 0.18 μg/g for retinol, 1.38 μg/g for vitamin D2 1.85 μg/g for vitamin K1 and 2.15 μg/g for vitamin K2. The Nigella sativa L. seeds were found to be rich in unsaturated fatty acids, vitamins and trace elements, suggesting that they may be valuable for apoptosis and would be appropriate to further studies in this direction.